Combination of (M)DSC and surface analysis to study the phase behaviour and drug distribution of ternary solid dispersions - Meeus, Joke; Scurr, David J.; Chen, Xinyong; Amssoms, Katie; Davies, Martyn C.; Roberts, Clive J.; Mooter, Guy Van den (Springer, 2015)
Purpose: Miscibility of the different compounds that make up a solid dispersion based formulation play a crucial role in the drug release profile and physical stability of the solid dispersion as it defines the phase behaviour of the dispersion. The standard technique to obtain information on phase behaviour of a sample is (modulated) differential scanning calorimetry ((M)DSC). However, for ternary mixtures (M)DSC alone is not sufficient to characterize their phase behaviour and to gain insight into the distribution of the active pharmaceutical ingredient (API) in a two-phased polymeric matrix. Methods: MDSC was combined with complementary surface analysis techniques, specifically time-of-flight secondary ion mass spectrometry (ToF-SIMS) and atomic force microscopy (AFM). Three spray-dried model formulations with varying API/PLGA/PVP ratios were analyzed. Results: The distribution of the API in the ternary solid dispersions depended on formulation parameters. The extent of API surface coverage and therefore the distribution of the API over both polymeric phases differed significantly for the three formulations. Conclusions: Combining (M)DSC and surface analysis rendered additional insights in the composition of mixed phases in complex systems, like ternary solid dispersions.